Effects of an eight-week proprioceptive neuromuscular facilitation stretching program on kicking speed and range of motion in young male soccer players - Akbulut, T.; Agopyan, A. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to determine the effect of the 8-week proprioceptive neuromuscular facilitation (PNF) exercises that were carried out on lower extremity on kicking speed and range of motion (ROM) performance in young soccer players. Twenty-four soccer players (15.6 ± 0.4 years) were selected from nonprofessional young soccer team. All players' height, weight, ROM (ankle plantar and dorsal flexions, hip flexions and extensions), and kicking speed tests were evaluated before and after 8 weeks. The participants were divided into PNF (n = 11) and control (n = 11) groups. Both groups continued technical and tactical soccer training together 3 days (120 min/d) a week. The PNF group attended additionally unassisted PNF-contract-relax (CR) stretching through 8 weeks, 2 days per week, 20 minutes' session duration. The control group did not participate in any additional PNF stretching sessions. There were significant differences in kicking speed, right ankle active dorsal flexion, and hip active flexion (right and left) (p = 0.05) of the PNF group, whereas there were no significant differences between groups in left ankle active dorsal flexion, hip active extension (right and left), and ankle active plantar flexion (right and left) (p > 0.05). We conclude that an 8-week unassisted PNF-CR improved on the ROM of particular lower extremity joints and the kicking speed in the young male soccer players. These results provide strength and conditioning coaches with a practical way to use unassisted PNF-CR in warm-up for positive improvements in the ROM of the hip and ankle and the applications of the kicking speed.